(untitled) (Journal of Applied Oral Science, 2021)
Hyperglycemia, a major characteristic of diabetes, is considered to play a vital role in diabetic complications. High glucose levels have been found to inhibit the mineralization of dental pulp cells. However, gene expression associated with this phenomenon has not yet been reported. This is important for future dental therapeutic application. Objective: Our study aimed to investigate the effect of high glucose levels on mineralization of human dental pulp-derived cells (hDPCs) and identify the genes involved. Methodology: hDPCs were cultured in mineralizing medium containing 25 or 5.5 mM D-glucose. On days 1 and 14, RNA was extracted and expression microarray performed. Then, differentially expressed genes (DEGs) were selected for further validation using the reverse transcription quantitative polymerase chain reaction (RT-qPCR) method. Cells were fixed and stained with alizarin red on day 21 to detect the formation of mineralized nodules, which was further quantified by acetic acid extraction. Results: Comparisons between high-glucose and low-glucose conditions showed that on day 1, there were 72 significantly up-regulated and 75 down-regulated genes in the high-glucose condition. Moreover, 115 significantly up- and 292 down-regulated genes were identified in the high-glucose condition on day 14. DEGs were enriched in different GO terms and pathways, such as biological and cellular processes, metabolic pathways, cytokine–cytokine receptor interaction and AGE-RAGE signaling pathways. RT-qPCR results confirmed the significant expression of pyruvate dehydrogenase kinase 3 (PDK3), cyclin-dependent kinase 8 (CDK8), activating transcription factor 3 (ATF3), fibulin-7 (Fbln-7), hyaluronan synthase 1 (HAS1), interleukin 4 receptor (IL-4R) and apolipoprotein C1 (ApoC1). Conclusions: The high-glucose condition significantly inhibited the mineralization of hDPCs. DEGs were identified, and interestingly, HAS1 and Fbln-7 genes may be involved in the glucose inhibitory effect on hDPC mineralization.